2010
DOI: 10.3122/jabfm.2010.03.080252
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Benefit of Complementary and Alternative Medicine (CAM) for Back Pain: A National Survey

Abstract: Background: Complementary and alternative medicine (CAM) is commonly used to treat back pain, but little is known about factors associated with improvement.Methods: We used data from the 2002 National Health Interview Survey to examine the associations between the perceived helpfulness of various CAM therapies for back pain.Results: Approximately 6% of the US population used CAM to treat their back pain in 2002. Sixty percent of respondents who used CAM for back pain perceived a "great deal" of benefit. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 34 publications
5
85
0
3
Order By: Relevance
“…Previous studies often have considered chiropractic as a therapy under complementary and alternative medicine (CAM). [15][16][17][18][19][20] The chiropractic profession reportedly has been viewed as having poor ethics and dishonesty when compared to other health care professions. 21 Organizations and authors have identified the lack of integration with mainstream health care as a major challenge for the chiropractic profession and have suggested strategies to overcome this barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies often have considered chiropractic as a therapy under complementary and alternative medicine (CAM). [15][16][17][18][19][20] The chiropractic profession reportedly has been viewed as having poor ethics and dishonesty when compared to other health care professions. 21 Organizations and authors have identified the lack of integration with mainstream health care as a major challenge for the chiropractic profession and have suggested strategies to overcome this barrier.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Despite a wide range of therapeutic modalities being offered by chiropractors, spinal manipulation (SM) is perceived to be the foundation of the chiropractic technique and is the most commonly used therapy by these health professionals. 3,4 SM is defined as a specific form of joint manipulation using either long-or shortleverage techniques targeting specific anatomic contacts or structures, and it is characterized by a low-amplitude dynamic thrust of controlled velocity, amplitude, and direction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is advisable to use this physiotherapeutic method in the daily practice of mentioned disease after careful selection. [16,17] CONCLUSION OTM application is a useful, harmless additional complementary treatment for the management of selected diseases. Our objective which was giving western trained physicians clinical applications of new Oncothermia-Booster method is fulfilled.…”
Section: Discussionmentioning
confidence: 99%